Conductive stretchable composites properly engineered to develop highly compliant electrodes for dielectric elastomer actuators. (4th September 2018) - Bele, Adrian; Tugui, Codrin; Asandulesa, Mihai; Ionita, Daniela; Vasiliu, Lavinia; Stiubianu, George; Iacob, Mihail; Racles, Carmen; Cazacu, Maria
Abstract: Carbon black (CB) particles were used as conductive filler for a high molecular weight polydimethylsiloxane- α, ω -diol (PDMS) to obtain conductive stretchable electrodes suitable for dielectric elastomer actuators. To ensure a perfect compliance between electrodes and the dielectric film, both based on the same PDMS, an original procedure consisting in their co-crosslinking was approached. Some of the Si–OH groups from the electrode solution will condensate with residual Si–OH groups from the surface of the dielectric elastomer (DE) creating chemical bridges. Electrode morphologies were examined by scanning electron microscopy, while their conductivities were evaluated by four-point method. Also, the electrodes influence on mechanical, viscoelastic and actuation properties on the resulted actuators was studied. Good results were obtained consisting in that the chemically bonded electrodes support large deformations (200%) without losing conductivity even after 10 000 cycles with no significant impact on the DE stiffness. The DE transducers exhibit electromechanical actuation of approximately 81% greater than that achieved with the same dielectric but with electrodes consisting of loose CB nanoparticles.